The Use of Photovoice Techniques to Explore Students’ Strategies in Learning English Vocabulary - Amrullah; Sudirman wilian; Sakinah, Nurul; Melani, Boniesta Zulandha (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2024)
This study aimed to investigate the vocabulary learning strategies used by students in learning English vocabulary and students’ problems faced in learning English vocabulary , particularly those in the English Education Study Program. This research used a descriptive qualitative method. The tools of data collection were Photovoice and Structured interviews. Researchers used thematic analysis for the study, here were steps of thematic analysis were Familiarizing with the data, Generating initial codes, Defining and Naming themes, and the last Producing the report. Based on data analysis, research results show that this research found that students use strategies in learning English vocabulary. particularly those students tend to rely more heavily on the